Customary Forests in West Papua: Contestation of Desires or Needs? - Ungirwalu, Antoni; Awang, San Afri; Runtuboi, Yubelince Y.; Peday, Mariana Y.; Marwa, Jonni; Maitar, Bustar; Murdjoko, Agustinus; Fatem, Sepus M (Forestry Faculty, Universitas Hasanuddin, 2021)
The challenge of integrating ecological, economic and social aspects of forest management is still a critical issue among stakeholders who agree on community-based forestry and the rights of indigenous peoples. In West Papua, the contrast of abundant natural resources with serious social inequalities and structured poverty is a continuing challenge for implementing a social forestry program. The process of establishing customary territories in West Papua is an important milestone in recognising its community entities. Is this scheme definitively able to answer the interests of access and management of indigenous peoples? This can help in achieving the sacred goal of protecting 70% of the forest area. This paper examines the dynamics of forest management in West Papua by the parties in customary forests. The low area designated for customary territories in West Papua, which has only reached 2,554.2 hectares, and the absence of a decree on the existence of customary forests is a form of injustice to the interests of local communities. The social forestry acceleration program intended to end the uncertainty surrounding customary forests is still in process. The roles of both on-site and off-site parties have not been optimal in realising customary forests in West Papua due to the complex and incomplete translation process at the site level. The results of the review show that interest is still focused on achieving an indicative-annual figure, which is still dominated by the village forest scheme. Hopefully, this year's acceleration of customary forests will become a milestone in West Papua, based on mutual need and desire.